Strategies to improve access for MSM in low-income and middle-income countries. Issue 5 (September 2019) - Rebe, Kevin; Hoosen, Nikhat; McIntyre, James A.
Abstract : Purpose of review: HIV prevention and treatment interventions for MSM are not well studied or reported from low-income and middle-income countries (LMIC) in comparison to those targeting gender-conforming populations. Some evidence-based strategies to engage MSM in appropriate healthcare have recently reported on their experiences and impact. Novel recruitment strategies have been developed for treatment and preexposure prophylaxis (PrEP) for MSM, leveraging new community engagement strategies and social media technologies. Recent findings: Despite publication of several new guidelines, there is little recent evidence available to guide MSM health programs in LMIC, highlighting the need for ongoing research and publication. Some important PrEP pilot study results have recently been published, such as the PrEP Brazil and Princess PrEP programmes, which could guide the scale-up of MSM PrEP. The novel use of technology and online platforms to strengthen MSM health delivery and support is particularly important. Summary: Providing healthcare to MSM requires consideration of context, broad stakeholder engagement, implementation of best practice guidelines and ongoing situational assessment and integration of novel community engagement methods that are evidence-based. Implementation of improved antiretroviral programmes and the access to PrEP for MSM are vital.